Atypical periodic paralysis and myalgia: A novel RYR1 phenotype. (30th January 2018) - Matthews, Emma; Neuwirth, Christoph; Jaffer, Fatima; Scalco, Renata S.; Fialho, Doreen; Parton, Matt; Raja Rayan, Dipa; Suetterlin, Karen; Sud, Richa; Spiegel, Roland; Mein, Rachel; Houlden, Henry; et al.
Abstract : Objective: To characterize the phenotype of patients with symptoms of periodic paralysis (PP) and ryanodine receptor ( RYR1 ) gene mutations. Methods: Cases with a possible diagnosis of PP but additional clinicopathologic findings previously associated with RYR1- related disorders were referred for a tertiary neuromuscular clinical assessment in which they underwent detailed clinical evaluation, including neurophysiologic assessment, muscle biopsy, and muscle MRI. Genetic analysis with next-generation sequencing and/or targeted Sanger sequencing was performed. Results: Three cases with episodic muscle paralysis or weakness and additional findings compatible with a RYR1 -related myopathy were identified. The McManis test, used in the diagnosis of PP, was positive in 2 of 3 cases. Genetic analysis of known PP genes was negative. RYR1 analysis confirmed likely pathogenic variants in all 3 cases. Conclusions: RYR1 mutations can cause late-onset atypical PP both with and without associated myopathy. Myalgia and cramps are prominent features. The McManis test may be a useful diagnostic tool to indicate RYR1 -associated PP. We propose that clinicopathologic features suggestive of RYR1 -related disorders should be sought in genetically undefined PP cases and that RYR1 gene testing be considered in those in whom mutations in SCN4A, CACNA1S, and KCNJ2 have already been excluded.